Wolnościowe podejście do pornografii i penalizacja niektórych jej postaci - Krajewski, Radosław (Studia Prawa Publicznego, 2025)
In the current state of the law, access to pornography is based on a freedom formula, as adults can view it if they wish. However, this does not apply to the presentation of pornographic content in public in such a way that could force viewing it on a person who does not wish to do so, as well as such content involving minors, with the presentation of violence and with the use of an animal. Both the libertarian approach to pornography and the criminalisation of these forms of pornography have different justifications, and the main aim of this study is to analyse and present them. They are relevant for a correct understanding of the scope of this criminalisation and, consequently, for the practice of criminal prosecution and justice. After all, acquaintance with pornographic content, its production and distribution is an area that is important both practically and dogmatically, yet these issues elude comprehensive cognition with an unjustified assumption of their clarity related to their established status in criminal law. There is therefore a need to reflect on them, both in terms of the scope of the regulation and in terms of the desired changes to it, which is the purpose of this study. In terms of the scope of the subject matter, the study attempts to provide a comprehensive picture of criminalisation in this area, but with the necessary limitations in terms of volume due to the study only taking the form of an article. In doing so, it aims to provide an original perspective on pornography.